2005
DOI: 10.1074/jbc.m411755200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Activates Human Lipocalin-type Prostaglandin D Synthase Gene Expression through De-repression of Notch-HES Signaling and Enhancement of AP-2β Function in Brain-derived TE671 Cells

Abstract: When the AP-2 element at ؊98 of the promoter region was deleted or mutated, the promoter activity was drastically decreased to ϳ10% of normal. The AP-2 element was bound by AP-2␤ dominantly expressed in TE671 cells, according to the results of electrophoretic mobility shift assay and chromatin immunoprecipitation assay. L-PGDS expression was induced by 12-O-tetradecanoylphorbol-13-acetate in TE671 cells, and this induction was inhibited by a protein kinase C inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 66 publications
1
30
1
1
Order By: Relevance
“…RNA Preparation and Quantification of RNA Level-Total RNA was extracted with Sepasol-RNAI (Nacalai Tesque, Kyoto, Japan), followed by further purification with an RNeasy Purification System (Qiagen, Hilden, Germany) (26). The firststrand cDNAs were synthesized from 1 g of total RNA with random hexamer and ReverTra Ace Reverse Transcriptase (Toyobo, Osaka, Japan) at 42°C for 60 min after the initial denaturation at 72°C for 3 min, followed by heat denaturation of enzyme at 99°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…RNA Preparation and Quantification of RNA Level-Total RNA was extracted with Sepasol-RNAI (Nacalai Tesque, Kyoto, Japan), followed by further purification with an RNeasy Purification System (Qiagen, Hilden, Germany) (26). The firststrand cDNAs were synthesized from 1 g of total RNA with random hexamer and ReverTra Ace Reverse Transcriptase (Toyobo, Osaka, Japan) at 42°C for 60 min after the initial denaturation at 72°C for 3 min, followed by heat denaturation of enzyme at 99°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…However, the transcriptional regulation of AP-2β is still unknown. It was recently reported that the transcriptional activity of AP-2α (another member of the AP2 family) is regulated by PKcµ, and that PKcα enhances the activation of AP-2β (30,31). These data led to us to hypothesize that PKcµ may regulate the activity of AP-2β in adipocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) assays were performed as described previously (7). Briefly, 3T3-L1 cells were caused to differentiate into adipocytes in the presence of the potent PPAR␥ agonist troglitazone (10 M) as the positive control for 6 days.…”
Section: Cell Culture Mouse Adipocytic 3t3-l1 Cells and Human Hela Cmentioning
confidence: 99%